Crown and crown-root fractures: an evaluation of the treatment plans for management proposed by 154 specialists in restorative dentistry - Monteiro de Castro, Mara Antonio; Poi, Wilson Roberto [UNESP]; Monteiro de Castro, Jose Carlos; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Trevisan, Carolina Lunardelli; Luvizuto, Eloa Rodrigues (Wiley-Blackwell, 2010)
Traumatic tooth injuries involve function and aesthetics and cause damage that range from minimal enamel loss to complex fractures involving the pulp tissue and even loss of the tooth crown. Technical knowledge and clinical experience are essential to establish an accurate diagnosis and provide a rational treatment. The purpose of this study was to evaluate the knowledge of Restorative Dentistry specialists about the management of crown and crown-root fractures based on treatment plans proposed by these professionals for these cases. A descriptive questionnaire was mailed to 245 Restorative Dentistry specialists with questions referring to their professional profile and the treatment plans they would propose for the management of crown and crow-root fractures resulting from dental trauma. One hundred and fifty-four questionnaires were returned properly filled. The data were subjected to descriptive statistics and the chi-square test was used to determine the frequency and the level of the significance among the variables. The analysis of data showed that in spite of having a specialist title, all interviewees had great difficulty in planning the treatments. As much as 42.8% of the participants were unable to treat all types of dental trauma. Complicated and uncomplicated crown-root fractures posed the greatest difficulties for the dentists to establish adequate treatment plans because these fractures require multidisciplinary knowledge and approach for a correct case planning and prognosis.